An Examination of the Negotiability Concept of the Uniform Commercial Code - John M. Feeney Jr.; Herbert L. Sherman Jr. (Washington University Law Quarterly, 1953)
The aim of this undertaking is to examine the impact, if any, that the new Uniform Commercial Code may have on our concept of negotiability as it has evolved to the present time. Analysis will be confined to this one broad topic, but our considerations are not limited to one section of the Code. Although analytical thought about the negotiability concept has been applied to its many segments, which we call rules, apparently nothing has been written on the Code that has emphasized the expansion of the concept itself which is now possible. The inspiration for this article stems from the ostensibly innocent words “within this article” found in Section 3-104 of the Uniform Commercial Code. It is contended that these words could completely change the historical policy of the courts and launch us into an entirely new era for the negotiability concept. A full understanding of this position can only be gained by an inquiry into the historical development of negotiability.
Keywords: Negotiable instruments; Commercial law; Bills and notes